2023
DOI: 10.3390/healthcare11050772
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 Vaccination Program Data Analysis Based on Regional Status and Day Type: A Study from West Java Province, Indonesia

Abstract: Vaccination is a strategy to control the COVID-19 pandemic and holds a crucial impact on global health. A better understanding of factors associated with vaccination is needed to establish a good vaccination program in a population. The purpose of this study is to analyze COVID-19 vaccination program data based on regional status and day type in the West Java Province of Indonesia and contribute to discovering other characteristics of the COVID-19 vaccination program. This study is a cross-sectional study usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 40 publications
0
6
0
1
Order By: Relevance
“…Indonesian people's perspectives of booster programmes show the dominance of positive sentiments towards vaccine boosters compared with negative sentiments [5,16]. A study found a significant difference in vaccination coverage and vaccination timing between cities and rural areas [5,16].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Indonesian people's perspectives of booster programmes show the dominance of positive sentiments towards vaccine boosters compared with negative sentiments [5,16]. A study found a significant difference in vaccination coverage and vaccination timing between cities and rural areas [5,16].…”
Section: Discussionmentioning
confidence: 99%
“…Indonesian people's perspectives of booster programmes show the dominance of positive sentiments towards vaccine boosters compared with negative sentiments [5,16]. A study found a significant difference in vaccination coverage and vaccination timing between cities and rural areas [5,16]. Because of national mandatory regulations and the demand for COVID-19 booster vaccinations in Indonesia, PT Bio Farma has developed a COVID-19 vaccine to help accomplish target vaccination for all populations globally, particularly in Indonesia [11,12].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations